Hepatic epithelioid hemangioendothelioma-report of three cases of a puzzling tumor - Nishika Madireddy; Megha S Uppin; Shantveer G Uppin; K R Harshavardhana; Venu Madhav; Meher Lakshmi Konatam (Wolters Kluwer Medknow Publications, 2022)
Hepatic epithelioid hemangioendothelioma (EHE) is a rare malignant vascular neoplasm with unpredictable clinical behavior. These lesions are frequently misdiagnosed owing to its non-specific symptomatology, ambiguous radiological features, and overlapping histomorphology. We report three cases of hepatic EHE, of which one was male and two were female patients. While all three patients presented with abdominal pain, the male patient gave an additional history of weight loss and was jaundiced. The radioimaging showed multiple nodules in the liver and two of the patients also had pulmonary metastasis. The biopsies of the liver nodules revealed a tumor composed of spindle, epithelioid, and stellate tumor cells, some with characteristic intracytoplasmic vacuolations/lumina surrounded by myxohyaline stroma. Some of these intracytoplasmic vacuoles/lumina showed erythrocytes, suggesting its vascular origin which was confirmed by CD31 and CD34 positivity. The article highlights the importance of histopathology and IHC in the precise diagnosis of EHE.